Percikan Najis dari Genangan Air Pembuangan; Studi Kasus Eksploratif Civitas Akademika UIN Alauddin Makassar - Alif, Muh. Rhesa; Musyahid, Achmad (Universitas Islam Negeri Alauddin Makassar, 2022)
Islamic law teaches a variety of taharah. Muslims in taharah are prescribed beristinja ', gargling, putting water in the nose, brushing teeth (siwak), shaving hair and so on. All activities carried out realize personal hygiene while anticipating the arrival of disease. To perform prayers and other ghairu mahdhah worship, Muslims are required to perform ablution. Wudhu in the sense of pure water that is clean from najis in addition to cleansing the lahiriyah also cleanses oneself internally, because prayer is an approach to Allah SWT